Sosialisasi Pengenalan Persyaratan Rumah Yang Aman dan Layak Huni Menurut SDGs (Sustainable Development Goals) - Jusuf Leiwakabessy; Putri Indah Cahyani; Sherly Lewerissa (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Considering that everyone has the right to have and obtain a prosperous life, decent housing, and a good and healthy living environment. To optimize regulation and realize livable houses and fulfillment of shelter, support in the form of regular and planned infrastructure, facilities, and public utilities is needed. Building inclusive, safe, durable, and sustainable villages is the 11th goal of the Sustainable Development Goals (SDGs). The socialization in Liang Village is an initiative undertaken to overcome the lack of public understanding regarding housing construction standards by SDGs. The main target of this activity is the Liang Village community. Socialization activities are carried out using 1 method, namely material presentation. The specific objectives of the socialization of livable housing requirements include increasing awareness of safe, healthy, and sustainable housing standards, as well as bringing positive changes in the behavior of planning and building houses.